The Use of Lymph Vessel Markers to Predict Endometrial Cancer Outcome. Issue 3 (1st April 2010) - Vandenput, Ingrid; Vanhove, Thomas; Calster, Ben Van; Gorp, Toon Van; Moerman, Philippe; Verbist, Godelieve; Vergote, Ignace; Amant, Frédéric
Abstract : Objective: To evaluate lymphangiogenesis and lymph vessel space involvement in different subsets of endometrial cancer using podoplanin, a specific marker for lymphatic endothelium. Methods: Sixty-two patients undergoing a hysterectomy with lymphadenectomy were included. Distribution of histopathologic subtypes was as follows: 30 endometrioid (48%), 18 serous (29%), 9 clear cell carcinoma (15%), and 5 carcinosarcomas (8%). Distribution of surgical stage according to the International Federation of Gynecology and Obstetrics 2009 criteria was as follows: 33 stage I (53%), 7 stage II (11%), 1 stage IIIA (2%), 15 stage IIIC1 (24%), and 6 stage IIIC2 (10%). Tumor samples were immunostained for podoplanin and the panendothelial marker, CD31. Peritumoral and intratumoral blood vessel density and lymph vessel density were assessed using an image analysis system that calculated mean vessel cross-sectional area (in micrometer squared) and vessel density (per millimeter squared). Presence of blood vessel space involvement and lymph vessel space involvement was screened for. The findings were linked with clinical outcome using Cox regression. Results: Twenty-one patients (34%) experienced recurrence, and 13 (21%) died of disease. Univariate analysis showed that blood vessel space involvement was related to worse overall survival (hazard ratio, 6.59; 95% confidence interval, 1.30-120). Multivariate analyses confirmed the prognostic importance of this variable for overall survival (hazard ratio, 7.52; 95% confidence interval, 1.32-144). Conclusion: Blood vessel space involvement is a prognostic marker for worse survival. Although lymph vessels were stained with the most reliable marker, podoplanin, lymph vessel density and lymphovascular space involvement do not seem to be of prognostic importance.